The Lebanese COVID-19 Cohort; A Challenge for the ABO Blood Group System - Khalil, Athar; Feghali, Rita; Hassoun, Mahmoud (Frontiers in Medicine, 2020)
A sudden outbreak of pneumonia caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has rapidly spread all over the world facilitating the declaration of the resultant disease as a pandemic on March 2020. Predisposing factors for acquiring COVID-19 and for developing a severe form of this disease were postulated to be related to the epidemiological, clinical, and genetic characteristics of the patients. Biological markers such as the ABO blood group system were amongst these factors that were proposed to be linked to the variability in the disease course and/or the prevalence of the infection among different groups. Herein, we conducted the first retrospective case-control study from the Middle East and North Africa that tackles the association between the blood group types and the susceptibility to, as well as the severity of, SARS-CoV-2 infection. Contrary to the most acknowledged hypothesis, our results challenged the significance of this association and questioned the role of the ABO blood group system in dictating the severity of this disease. For future similar studies, we endorsed analyzing larger cohorts among different populations and we encouraged implementing more rigorous approaches to diminish the potential confounding effect of some underlying comorbidities and genetic variants that are known to be associated with the ABO blood group system.